Management of HIV in pregnancy. Issue 7 (July 2018) - Hamlyn, Eleanor; Barber, Tristan J.
Abstract: A cohesive multidisciplinary team approach is key in the management of HIV in pregnancy. The primary aim is to prevent transmission to the neonate but also to support the mother in any issues arising from her pre-existing, or new, diagnosis of HIV. Specialist advice should be sought, wherever possible. Key areas discussed in this review include antenatal management of the mother (particularly pharmacological management), obstetric management, pharmacological treatment for the neonate and infant feeding. Due to progress made in both in HIV testing, and in the way all patients with HIV in the UK are managed over the last few decades, most women who present with HIV in pregnancy are aware of their diagnosis and on treatment. However, it is not entirely uncommon for women to be diagnosed in pregnancy and it is these cases that present the greater challenge. The cases in this review cover the most common scenarios encountered.